Analysis of clinical and methodological characteristics of early COVID-19 treatment clinical trials - Mainoli, Beatrice (2021)
Mainoli, B., Machado, T., Duarte, G. S., Prada, L., Gonçalves, N., Ferreira, J. J., & Costa, J. (2021). Analysis of clinical and methodological characteristics of early COVID-19 treatment clinical trials: so much work, so many lost opportunities. BMC Medical Research Methodology, 21(1), 1-10. [42]. https://doi.org/10.1186/s12874-021-01233-w